2019
DOI: 10.1590/01047760201925032642
|View full text |Cite
|
Sign up to set email alerts
|

ENDOPHYTIC FUNGI COMMUNITY IN Eremanthus erythropappus TREE FROM ANTHROPOGENIC AND NATURAL AREAS OF MINAS GERAIS

Abstract: Natural habitat was the area with the highest number of endophytic fungi genera recovered from E. erythropappus Some genera of endophytic fungi from E. erythropappus showed antagonism against phytopathogenic fungi The most of the endophytic fungi isolated from E. erythropappus belong to the Ascomycota phylum S. sclerotiorum was the most sensitive phytopathogen inhibited by endophytic fungi isolated from E.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…For example, most fungi and bacteria associated with plants are barely known in the region [ 5 , 6 ]. Among these communities, the fungi communities associated with plants are particularly important because they have a strong symbiotic relationship that supports plant growth [ 7 , 8 ] helping to defend them against pathogens [ 9 , 10 ]. Fungi are instrumental in carbon and nitrogen cycling and participate in the bioremediation of xenobiotics [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, most fungi and bacteria associated with plants are barely known in the region [ 5 , 6 ]. Among these communities, the fungi communities associated with plants are particularly important because they have a strong symbiotic relationship that supports plant growth [ 7 , 8 ] helping to defend them against pathogens [ 9 , 10 ]. Fungi are instrumental in carbon and nitrogen cycling and participate in the bioremediation of xenobiotics [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Endophytic fungal communities are ubiquitous and many of them are essential for the adaptation of their host plants to specific environments, such as recovery areas from mining activities. These microorganisms grow asymptomatically in root cells, stems and leaves and are significant mutualists, increasing the uptake of nutrients by physical and chemical means [ 7 , 14 ]. Studies on the diversity of endophytic fungi have shown that a single plant can be colonized by more than 1000 microbial species, and most of them cannot be cultivated [ 12 ].…”
Section: Introductionmentioning
confidence: 99%